Response of wheat growth, grain yield and water use to elevated CO 2 under a Free‐Air CO 2 Enrichment ( FACE ) experiment and modelling in a semi‐arid environment - Garry J. O'Leary; Brendan Christy; James Nuttall; Neil Huth; Davide Cammarano; Claudio Stöckle; Bruno Basso; Iurii Shcherbak; Glenn Fitzgerald; Qunying Luo; Immaculada Farre‐Codina; Jairo Palta; et al. (Global Change Biology, 2015)
The response of wheat crops to elevated CO 2 ( eCO 2 ) was measured and modelled with the Australian Grains Free‐Air CO 2 Enrichment experiment, located at Horsham, Australia. Treatments included CO 2 by water, N and temperature. The location represents a semi‐arid environment with a seasonal VPD of around 0.5 kP a. Over 3 years, the observed mean biomass at anthesis and grain yield ranged from 4200 to 10 200 kg ha −1 and 1600 to 3900 kg ha −1 , respectively, over various sowing times and irrigation regimes. The mean observed response to daytime eCO 2 (from 365 to 550 μmol mol −1 CO 2 ) was relatively consistent for biomass at stem elongation and at anthesis and LAI at anthesis and grain yield with 21%, 23%, 21% and 26%, respectively. Seasonal water use was decreased from 320 to 301 mm ( P = 0.10) by eCO 2 , increasing water use efficiency for biomass and yield, 36% and 31%, respectively. The performance of six models (APSIM‐Wheat, APSIM‐Nwheat, CAT‐Wheat, CROPSYST , OLEARY ‐ CONNOR and SALUS ) in simulating crop responses to eCO 2 was similar and within or close to the experimental error for accumulated biomass, yield and water use response, despite some variations in early growth and LAI . The primary mechanism of biomass accumulation via radiation use efficiency ( RUE ) or transpiration efficiency ( TE ) was not critical to define the overall response to eCO 2 . However, under irrigation, the effect of late sowing on response to eCO 2 to biomass accumulation at DC 65 was substantial in the observed data (~40%), but the simulated response was smaller, ranging from 17% to 28%. Simulated response from all six models under no water or nitrogen stress showed similar response to eCO 2 under irrigation, but the differences compared to the dryland treatment were small. Further experimental work on the interactive effects of eCO 2 , water and temperature is required to resolve these model discrepancies.